Sensory evaluation of a snack food manufactured from coconut residue flour - Suarez, Andres B. T.
The effects of amount of coconut residue flour (CRF), amount of water and the fact content of CRF on the sensory properties of snack chips were studied in two phases. Phase I involved the determination of the effects of amount of CRF (0%, 15%, 30%) substitution of the wheat flour and water (45%, 50%, 55%). In phase II, the effects of the fat content of CRF (23%, 28%, 33%) and increased amounts of CRF (20%, 35%, 50% substitution of wheat flour) were investigated. Twenty-four panelists evaluated all samples for color lightness, saltiness, coconut flavor, spicy flavor, hardness, and crunchiness. Results indicated significant effect of amount of CRF and water in the formulation on color lightness, coconut flavor, spiciness, hardness, and crunchiness of chips. Increased fat content in CRF with increased amount of CRF in the formulation significantly affected all attributes of the product.